Skipping Skippable Ads on YouTube: How, When, Why and Why Not? - Banerjee, Snehasish; Pal, Anjan (2021 15th International Conference on Ubiquitous Information Management and Communication (IMCOM), 2021)
YouTube introduced skippable video ads, which give Internet users the option to skip the ads after a 5-second non-skippable segment. This interactive format has now become dominant in the industry as it offers greater control to the audience. However, if users always skip skippable ads, the advertisers' purposes would not be served. Bombarding users with long-duration non-skippable ads is also not a viable option as it can result in negative user experiences. On the scholarly front, this problem has mostly been tackled using quantitative studies. The literature still lacks an in-depth understanding of users' perceptions of skippable ads. Hence, adopting a qualitative lens of investigation, this research explores users' responses toward skippable ads. Using in-depth interviews, it investigates (1) how, (2) when, (3) why, and (4) why not users skip skippable ads. Themes related to the question of "how" include habitual skipping and emotional skipping. Regarding the question of "when", a few respondents would have liked to skip even before five seconds. About half of the respondents thought that the non-skippable duration of five seconds was reasonable but they would skip as soon as skipping is allowed. Occasionally, some respondents were open to consider a longer duration of non-skippability. Skippable ads are skipped due to repetitions, time constraints, lack of personalization, and users' negative attitudes towards advertising. In contrast, they are not skipped if they are captivating and personalized. Additionally, when users are in a relaxing mood, skippable ads may not be skipped. The contributions of the findings are discussed.